FACTORS IN THE USE OF SOCIAL NETWORKS IN PUBLIC ADMINISTRATION - D. , Hryn (Theory and Practice of Public Administration, 2021)
Factors in the use of social networks in public administrationThe use of social networks is slowly growing and evolving in government, but too often they are still considered a whim. From a scientific and practical point of view, it is interesting in recent years to find out what stimulates the introduction of social networks in the public sector.According to this, the aim of the study was to substantiate the composition of factors that stimulate the use of social networks in the public authorities’ activity.The article analyzes the features of functioning and the main directions of application of social network technologies in public administration. The list and internal conditions of stimulating factors formation of social networks in public management are investigated. Particular attention is paid to a more detailed consideration of behavioral, technological and economic factors influencing the introduction of social networks in the public sector. It is proved that these stimulating factors create preconditions for better development of social networks and expand their applicability in public administration.It is also noted that the influence of incentives may be faced by certain barriers to the use of social networks in the public sector. The introduction of social technologies can be complicated by numerous problems, central of them are four: 1) systemic challenges, including the fact that power is highly distributed in the system of public administration; 2) organizational and cultural challenges related to bureaucracy and existing standard operating procedures; 3) information challenges related to the processes of verification and substantiation of information; and 4) legal challenges related to the use of innovative (and relatively untested) technologies in the public sector. In order to moderate such impacts, participation and cooperation in public governance of citizens and businesses should be encouraged, and social networking technologies should be seen as excellent tools to encourage participation and collaboration.